1981. Implementation of an Antifungal Stewardship Bundle Focused on Candidemia in an Indian Hospital - Moni, Merlin (Open Forum Infect Dis, 2019)
BACKGROUND: In India, Candida bloodstream infections have a reported incidence of 1–12 per 1,000 admissions and a mortality rate of up to 60%. Antimicrobial stewardship programs (ASP) can improve quality of care and clinical outcomes. This study evaluates the impact of a comprehensive candidemia ASP bundle in a hospital in southern India with an established stewardship program. METHODS: A single-center, pre-post quasi-experimental study was conducted at a tertiary-care center in southern India to analyze the impact of an ASP care bundle for the management of adults with candidemia. During the intervention period (October 2017–December 2018), the ASP provided recommendations to providers in accordance with the 2016 IDSA Guidelines for the Management of Candidemia, which included the following bundle: (1) appropriate selection and dosing of antifungal therapy; (2) repeat blood cultures every 48 hours until clearance; (3) removal of central venous catheters and other potential removable foci of infection; (4) echocardiogram; (5) ophthalmologic evaluation; and (6) appropriate duration of therapy. The primary outcome was initiation of appropriate antifungal therapy. Additional clinical outcomes were also compared with a historical cohort. RESULTS: One hundred and four patients with candidemia were included: 52 in the pre-intervention and 52 in the post-intervention group. Overall, baseline demographics were similar between the two groups (Table 1). Candida tropicalis (26.9%) and Candida parapsilosis (29.8%) were the most common causes of candidemia in the cohort. Following intervention, administration of appropriate antifungal therapy improved by 40.4% (28.8% pre vs. 69.2% post, P < 0.01). Average time to effective treatment initiation following culture positivity decreased from 57.6 hours to 12 hours in the post-intervention group (P < 0.01). Thirty-day all-cause mortality was similar between the two groups (34.6% 38.4%, P = 0.84). CONCLUSION: Implementation of a comprehensive candidemia care bundle by the ASP significantly improved the use and timing of initiation of appropriate antifungal therapy. [Image: see text] DISCLOSURES: All authors: No reported disclosures.